Physical activity is associated with exercise capacity among patients undergoing chemotherapy: A pilot randomized controlled trial - Alexis Antonucci; Alexander R. Lucas; Juliana Costa; Sam Norton; Peter Brubaker; Shannon Mihalko; Alexandra Marshall; Jeremy Via; R. Lee Franco; Amy Ladd; Rakhee Vaidya; Victor Yazbeck; et al. (PLoS ONE, 2025)
Introduction Exercise intolerance is common among cancer patients undergoing active treatments. We conducted a pilot study in patients receiving potentially cardiotoxic therapies to investigate the impact of participation in a 6-month physical activity intervention (PAI) versus a healthy lifestyle education control intervention (HLI) on accelerometer-derived measures of PA (steps/day or minutes of moderate to vigorous PA [MVPA]/week) and whether these measures were associated with submaximal exercise capacity (6-minute walk distance [6MWD]). Methods Participants with breast cancer or lymphoma (n = 33) were randomized (2:1) into PAI or HLI groups. Exercise training was patient-centered, tailored by treatment and functional status. Objective assessments of PA (steps/day, MVPA/week), and submaximal exercise capacity (6MWD) were completed at baseline, 3-, and 6-months. Descriptive statistics were used to examine changes in PA and 6MWD. T-tests were used to examine differences in 6MWD between groups at 3- and 6-months. Results At baseline, 27 participants in the PAI (n = 20) and HLI (n = 7) groups who completed baseline and at least 1 follow up visit, had a mean age of 53 (range: 23–76) vs 56 (range: 40–77) years, took on average 8,330 ± 2520 vs 7800 ± 3830 steps/day, did an average of 133 ± 44 vs 109 ± 87 minutes of MVPA/week, and had a mean 6MWD of 496 ± 94 vs 440 ± 18 meters, respectively. At 3- and 6-months there was a 87m and 76m difference in 6MWD by intervention group. A correlation analysis did find significant associations between steps/day (r = 0.51, p = .04) and 6MWD at 3-months. Conclusions Baseline data indicate that, on average, our study sample was close to meeting the PA guidelines. Unexpectedly, both groups maintained their activity levels up to 3- and 6-months. Submaximal exercise capacity (6MWD) was also maintained (with a clinically meaningful but not statistically significant relative benefit in the PAI) suggesting higher PA levels may associate with reduced exercise intolerance after anthracycline therapy.